2007
DOI: 10.1007/s10701-007-9162-4
|View full text |Cite
|
Sign up to set email alerts
|

A Nonconventional Scenario for Thermal Equilibrium

Abstract: A nonuniform superconducting loop poses a challenge to statistical mechanics: assuming thermal equilibrium and applying the accepted rules, we obtain that the heat flow does not vanish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…
More than a decade ago I considered a model that represented a discretized superconducting loop with nonuniform thickness. The temperature of the loop was uniform but, nevertheless, I found that, in equilibrium, there is still heat flow along the ring [1]. Here I report two required corrections to the hypotheses of that study.The first correction required is in Eq.
…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…
More than a decade ago I considered a model that represented a discretized superconducting loop with nonuniform thickness. The temperature of the loop was uniform but, nevertheless, I found that, in equilibrium, there is still heat flow along the ring [1]. Here I report two required corrections to the hypotheses of that study.The first correction required is in Eq.
…”
mentioning
confidence: 75%
“…k 2k B T σw k N/L∆t, where η A k stands for a random variable with zero average, variance 1 and normal distribution, and all the definitions made in [1] still apply.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Gordon [39][40][41][42] and J. Denur [43][44][45][46]. By the mid-1990s, the number and variety of challenges mushroomed as multiple research teams entered the field, includingČápek et al [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], Allahverdyan and Nieuwenhuizen [62][63][64][65][66], Berger [67,68], Crosignani et al [69][70][71][72][73], Keefe [74][75][76], Nikulov and Dubonos et al [77][78][79], and Miller [80]. During the last 20 years, more than a half-dozen challenges have been investigated at University of San Diego (USD), covering the fields of plasma, chemical, gravitational, biological and solid state physics [9][10][11][81]…”
Section: Second Law Challengesmentioning
confidence: 99%